PENGARUH SISTEM INFORMASI AKUNTANSI PEMBERIAN KREDIT DAN EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN (Studi Kasus pada Koperasi Simpan Pinjam Artha Jaya Makmur Surakarta) - Djoko Kristianto, Catur Kristanto, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the significance of accounting information systems influence the granting of credit and the effectiveness of the internal control system partially and simultaneously on performance of employees in a Cooperative Loan (KSP) Artha Jaya Prosperous Surakarta.. Populations and samples in this study are all employees of the internal audit section, part of a Ministry, part of the credit, part public, part credit supervision and accounting section on Cooperative Loan (KSP) Artha Jaya Makmur Surakarta totaling 26 employee. Data analysis techniques using multiple linear regression, t-test, F-test, and the coefficient of determination. The research results obtained the conclusion that there is a significant influence on the accounting information system of granting of credit and the effectiveness of internal control systems simultaneously on performance of employees in a Cooperative Loan (KSP) Artha Jaya Makmur Surakarta.Keywords: accounting information systems, the effectiveness of the internal control system, employee performance